EhVps23: A Component of ESCRT-I That Participates in Vesicular Trafficking and Phagocytosis of Entamoeba histolytica - Galindo, Ausencio; Javier-Reyna, Rosario; García-Rivera, Guillermina; Bañuelos, Cecilia; Montaño, Sarita; Ortega-Lopez, Jaime; Chávez-Munguía, Bibiana; Salazar-Villatoro, Lizbeth; Orozco, Esther (Frontiers in Cellular and Infection Microbiology, 2021)
The endosomal sorting complex required for transport (ESCRT) is formed by ESCRT-0, ESCRT-I, ESCRT-II, ESCRT-III complexes, and accessory proteins. It conducts vesicular trafficking in eukaryotes through the formation of vesicles and membrane fission and fusion events. The trophozoites of Entamoeba histolytica, the protozoan responsible for human amoebiasis, presents an active membrane movement in basal state that increases during phagocytosis and tissue invasion. ESCRT-III complex has a pivotal role during these events, but ESCRT-0, ESCRT-I and ESCRT-II have been poorly studied. Here, we unveiled the E. histolytica ESCRT-I complex and its implication in vesicular trafficking and phagocytosis, as well as the molecular relationships with other phagocytosis-involved molecules. We found a gene encoding for a putative EhVps23 protein with the ubiquitin-binding and Vps23 core domains. In basal state, it was in the plasma membrane, cytoplasmic vesicles and multivesicular bodies, whereas during phagocytosis it was extensively ubiquitinated and detected in phagosomes and connected vesicles. Docking analysis, immunoprecipitation assays and microscopy studies evidenced its interaction with EhUbiquitin, EhADH, EhVps32 proteins, and the lysobisphosphatidic acid phospholipid. The knocking down of the Ehvps23 gene resulted in lower rates of phagocytosis. Our results disclosed the concert of finely regulated molecules and vesicular structures participating in vesicular trafficking-related events with a pivotal role of EhVps23.